A newly-developed wide range molecular flow meter based on AAO leak element. (March 2020) - Wang, Xudi; Wang, Hao; Hua, Yu; Cao, Qing; Bi, Hailin; Zhang, Jun; Yu, Zhenhua; Wei, Wei
Abstract: A n innovate constant volume flow meter (ICVFM) using AAO leak element was developed, and then applied to measure the pumping speed of dry vacuum pumps. The AAO leak element was calibrated with dynamic differential pressure decay method. The results imply that the conductance of AAO leak is inversely proportional to the square root of the molecular mass, and remains unchanged with pressure varying from vacuum to atmosphere. Then the pumping speed was measured by a simple test system. In the end, the uncertainties of calibrating AAO leak element and measuring pumping speed were considered to confirm the measurement capability. The newly developed flow meter enables flow measurements at pressures ranging from vacuum through atmospheric pressure, which has potential application in the semiconductor industry. Highlight: A newly-developed wide range molecular flow meter using anodic aluminum oxide(AAO). In the assembly, AAO is supported by porous metal to prevent collapse. Innovate constant volume flow meter has a wide measurement range, from molecular flow regime to continuum flow regime. Pumping speed measurement using innovate constant volume flow meter.